Creatine kinase, an ATP-generating enzyme, is required for thrombin receptor signaling to the cytoskeleton - Mahajan, Vinit B. (The National Academy of Sciences, 2000)
Thrombin orchestrates cellular events after injury to the vascular system and extravasation of blood into surrounding tissues. The pathophysiological response to thrombin is mediated by protease-activated receptor-1 (PAR-1), a seven-transmembrane G protein-coupled receptor expressed in the nervous system that is identical to the thrombin receptor in platelets, fibroblasts, and endothelial cells. Once activated by thrombin, PAR-1 induces rapid and dramatic changes in cell morphology, notably the retraction of growth cones, axons, and dendrites in neurons and processes in astrocytes. The signal is conveyed by a series of localized ATP-dependent reactions directed to the actin cytoskeleton. How cells meet the dynamic and localized energy demands during signal transmission is unknown. Using the yeast two-hybrid system, we identified an interaction between PAR-1 cytoplasmic tail and the brain isoform of creatine kinase, a key ATP-generating enzyme that regulates ATP within subcellular compartments. The interaction was confirmed in vitro and in vivo. Reducing creatine kinase levels or its ATP-generating potential inhibited PAR-1-mediated cellular shape changes as well as a PAR-1 signaling pathway involving the activation of RhoA, a small G protein that relays signals to the cytoskeleton. Thrombin-stimulated intracellular calcium release was not affected. Our results suggest that creatine kinase is bound to PAR-1 where it may be poised to provide bursts of site-specific high-energy phosphate necessary for efficient receptor signal transduction during cytoskeletal reorganization.